Entre a França e o Brasil: criação, circulação e apropriações do Método Francês de Educação Física (1931-1960) - Bruschi, Marcela (2019)
This work aims at understanding the French Method constitution process in France and the aspects of its circulation in Brazil. The research heads into the direction of finding strategies and tactics that enabled this model to dent in Brazil and forge Physical Education. It dialogues with the Cultural History precepts (BLOCH, 2001; CHARTIER, 2002; CERTEAU, 1982, 1994) and the Italian Micro-History (GINZBURG, 1991, 1999, 2002a, 2002b) in order to think about the questions that involve: dialogues with the national and international production regarding the French Method creation aspects and its introduction in Brazil; interlocutions with the New School movement in Europe and their interfaces with the Physical Education in France; the French Method creation process and its eclecticism strategy; aspects concerning its arrival, development and diffusion in Brazil; Physical Education Teachers’ training; and schooling experiences with the French Method. The documental corpus is constituted of sources located in France and in Brazil, decrees, newsletters, manuals, printed matters, books, military documents, and official documents of Teachers’ training courses, among others. The work considers that the French Method constitution involved strategies and tactics with the purpose to create a method considered national in France, accepting the eclecticism as to determine the place of power belonging to École de Joinville-le-Pont, incorporating knowledge and practices of the other Physical Education methods and systems ongoing in France and Europe: the Swedish Method, the Natural Method, the English sports and the Georges Demeny’s system. Wisely, the research also incorporates the New School updated educational expectations and desire and from the other fans who used to struggle for a more modern Physical Education. Its infusion within Brazil is also seen, in a strategically and tactically way, related to new educational perspectives of the New School movement, with nationalist desire and with Brazilianness’ feelings. At the same time, it projected a greater professional qualification of the Physical Education Teachers, subjects who were able to operate new uses with the circulating model.